*-Jordan-type maps on C*-algebras. Issue 12 (2nd December 2021) - Macedo Ferreira, Bruno Leonardo; Costa, Bruno Tadeu
Abstract: Let A and A ′ be two C * -algebras with identities I A and I A ′, respectively, and P 1 and P 2 = I A − P 1 nontrivial symmetric projections in A . In this paper we study the characterization of multiplicative * -Jordan-type maps. In particular, if M is a factor von Neumann algebra then every bijective unital multiplicative * -Jordan-type maps are * -ring isomorphisms.